Representation of the Other Reproduce Inequalities: A Case Study of the Dictator Film in Terms of Orientalism (Journal of Advanced Research in Social Sciences, 2021)
Representing the other in media is the process of exchanging culture, it gives us information about the unknown, ‘the other’ creating a certain image about them, this image evolves till it becomes their stereotype. Stereotypes are a form of media representation, which is often inaccurate, negative, partial and limited. Which is what happened with the Orient, as Edward Said in his pioneer work ‘Orientalism’ explains. This article focuses on the formation of stereotypes and misrepresentations of the Arabs in Hollywood movies taking Larry Charles’s film dictator (Charles, 2012) as a case study. The paper argues that increasing the representation of the other can reproduce inequality as it was the case in the film. The paper applies Edward Said’s Orientalism and Stuart Hall’s work to shed the light on the traditional stereotype of representing Arabs in the film. Textual analysis is used to analysis the representation of the character traits of the protagonists and the representation of the Arab countries in relation to Orientalism. The paper will focus on the representation of the character traits of the protagonist, representation of Arab countries in relation to Orientalism and creation of stereotypes.